Milestones in North Carolina librarianship (From the president [column]) - Jones, Plummer Alston (East Carolina University, 2000)
This article highlights recent accomplishments and awards earned by North Carolina libraries and librarians.
Keywords: Librarianship; Libraries--North Carolina; Awards; Column